Critical evaluation of the necessary changes of the interaction of employers, employees, local authorities, state and other stakeholders of the education system - Dzelme, Juris; Sloka, Biruta; Tora, Ginta; Buligina, Ilze (University of Latvia, 2020)
Expansion of business creates globalization, which should be balanced by the localization and development of adequate changes in education. Aim of the paper is to find the ways to solve the social problems linked with the globalization. The review of the existing problems reveals many shortcomings of the classical “free market” theory. The increased speed of exchange of information demands special care to improve the accessibility and quality of education, using life-long learning and distance education. The appropriate attitudes, skills and knowledge should be proposed to support innovations, localization of economics and organization of interaction between employers, employees and other involved parties (state authorities, local communities) to cope with the future challenges. Research methods used in this paper are scientific publications and previous research analysis, statistical data analysis for the critical evaluation of social structure, interaction of people and possibilities for the cooperation. The dispersed knowledge, necessary for the successful action of economics belong to different actors. Creation of trust between all involved actors becomes more important now. Education must give not only skills and knowledge, but also attitudes and morality. All stakeholders of the education system should participate to support changes in education and lifelong learning according to the fast changes in the social structure. The main part of the interaction should be informal. Cooperation and negotiations, using local networks, are the most effective way to receive the knowledge and skills and to create trust and motivation. Innovations should be linked with the development of local networks and other necessary changes in the social structure. Informal regulations, trust and morality should support management. Humanities, art and philosophy must be used by the education system to form the attitudes and motivation.
Keywords: innovations; attitudes; knowledge; skills; lifelong learning; Research Subject Categories::SOCIAL SCIENCES::Business and economics